Pengujian Aplikasi Accounting Pencatatan Keuangan Distribusi Keripik Pisang Menggunakan Metode Black Box - Frendi Triarista; Sidiq Abdul Rahman; Aries Saifudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
This study examines the implementation and evaluation of the Black Box method in testing an accounting application in the banana chip production industry. The primary objective of this research is to assess the performance and accuracy of the application in recording financial and production transactions. The Black Box method, which solely inspects input and output without considering the internal processes of the application, is utilized in this context to evaluate the effectiveness and efficiency of the application. The study involved collecting data from various financial and production transactions in the banana chip industry, which were then input into the application. Testing using the Black Box method was conducted by examining whether the output generated by the application met the expected outcomes based on the given inputs. The results of the research indicate that the application was successful in recording and processing data with a high level of accuracy, achieving good efficiency in company operations. However, several areas for improvement were identified, particularly related to the handling of complex transaction data. This study affirms that the Black Box method is effective in application testing and demonstrates its potential in enhancing the efficiency of financial recording applications. Recommendations for further research and implementation in other sectors are also presented.